Fludarabine Treatment of Patient with Chronic Lymphocytic Leukemia Induces a Digital Ischemia - Soyaltin, Utku Erdem; Yuce Yildirim, Deniz; Yildirim, Mustafa; Ugur, Mehmet Can; Ekinci, Ferhat; Ceylan, Cengiz; Akar, Harun (Case Reports in Hematology, 2016)
We report a 63-year-old man with a history of chronic lymphocytic leukemia (CLL) who presented with asymmetrical Raynaud’s phenomenon of sudden onset which progressed to acral gangrene rapidly in a week. These symptoms began approximately one week after the fourth cycle of fludarabine and cyclophosphamide chemotherapy and were accompanied by pain, numbness, and cyanosis in the fingers of his right hand except the first finger. Fludarabine may play a role in acral vascular syndrome. The treatment with fludarabine in patients with evolving digital ischemia should be carried out with caution.